Sex-Related Differences in the Incidence, Severity, and Recovery of Concussion in Adolescent Student-Athletes Between 2009 and 2019. Issue 7 (June 2021) - Hannah, Theodore C.; Li, Adam Y.; Spiera, Zachary; Kuohn, Lindsey; Dai, Jennifer; McAuley, Fiona; Ali, Muhammad; Durbin, John R.; Dreher, Nickolas; Marayati, Naoum Fares; Gometz, Alex; Lovell, Mark; et al.
Background: The sex of an athlete is thought to modulate concussion incidence; however, the effects of sex on concussion severity and recovery are less clear. Purpose: To evaluate sex differences in concussion severity and recovery using a large, heterogeneous sample of young student-athletes with the goal of understanding how sex affects concussion outcomes in young athletes. Study Design: Cohort study; Level of evidence, 3. Methods: The Immediate Post-Concussion Assessment and Cognitive Testing results of 11, 563 baseline and 5216 postinjury tests were used to calculate the incidence of concussion of adolescent male and female student-athletes ages 12 to 22 years (median, 15 years). The postinjury tests of 3465 male and 1751 female student-athletes evaluated for concussion or head trauma were used to assess differences in the Severity Index (SI) and recovery. Chi-square tests and t tests were used to compare differences in demographic characteristics, incidence, and SI between the 2 cohorts. Multivariable linear, logistic, and Cox proportional hazards regressions were used to control for differences between cohorts in analyses of incidence, SI, and recovery. Results: When we controlled for demographic differences, female participants had higher odds of concussion (odds ratio, 1.62; 95% CI, 1.40-1.86; P < .0001) and higher SI after concussion (β = 0.67; 95% CI, 0.02-1.32; P = .04). This discrepancy in SI was a result of differences in Symptom (2.40 vs 2.94; P < .0001) and Processing Speed (0.91 vs 1.06; P = .01) composite scores between male and female participants, respectively. We found no effect of sex on time to recovery when controlling for initial concussion SI (hazard ratio, 0.94; 95% CI, 0.78-1.12; P = .48). Conclusion: Using large, multisport cohorts, this study provides evidence that female athletes are at higher risk for more concussions and these concussions are more severe, but male and female athletes have similar recovery times when the analysis controls for initial concussion SI.